Redistribution, state trading enterprises and 'politically optimal' tariffs. (November 2013) - McCorriston, Steve; MacLaren, Donald
Abstract State trading enterprises (STEs) are widely used and can be viewed as instruments of trade policy. We analyse two aspects: the first is their potential trade distorting effect; the second is how they modify the case for the 'politically optimal' tariff. We show that the STE can reduce the need for a tariff designed for domestic redistribution. This result introduces some ambiguity about how STEs are interpreted: from a multilateralist perspective, they should be dealt with in the same way as other non‐tariff barriers; from a nationalistic perspective, they can reduce the need for 'politically optimal.'